Lexical retrieval for nouns and verbs in typically developing bilectal children - Kambanaros, Maria; Grohmann, Kleanthes K.; Michaelides, Michalis P. (My University, 2013)
Previous evidence shows that nouns are easier for many language users to retrieve than verbs, but scant research has been conducted with children in bilectal environments (where both standard and non-standard forms of a language are spoken). This study investigates object and action naming in children who are native speakers of a nonstandard variety, Cypriot Greek (CG), but instructed scholastically in the official variety, Standard Modern Greek (SMG). Participants were typically developing Greek Cypriot preschoolers and early school-aged children who completed the Cypriot Object and Action Test (COAT). Results revealed a significant grammatical word class effect favoring nouns over verbs in Modern Greek, with a developmental change in the size of the noun–verb gap. Both age groups showed similar error patterns for both object and action targets. For action names, children produced more semantic descriptions or circumlocutions (e.g., hitting the nail for hammering), whereas omissions were the prominent error type for object names. The findings are discussed in relation to crosslinguistic evidence of grammatical word class differences using the picture naming paradigm for monolingual (pre)school-aged children.
Keywords: Bi(dia)lectism/bilingualism; Cypriot Greek (CG); Cypriot Object and Action Test (COAT); Grammatical category; Nouns; Picture naming task; Semantic errors; Standard Modern Greek (SMG); Typical language development; Verbs